Glimpses of Contribution of Khawaja Khan Muhammad (RA) in Effecting Spiritual Transformation in Society - Ghaffar, Dr. Abdul (Al-Amīr Research Journal for Islamic Studies, 2024)
Pakistan came into being in 1947. The new formed state needed not only construction of infrastructure but also political and ideological grooming. Pakistan was established as an Islamic State. In order to be a truly representative Islamic State, spiritual transformation of its individuals was needed. For this purpose, a good number of Ulema migrated from the eastern part of the subcontinent to Pakistan after the partition. The Khanqahi system in the subcontinent and beyond subcontinent has been extending its valuable services to the Muslim Ummah for centuries. Among various Muslim Sufi fraternities, Naqshbandīyah Mujaddidia order has been working hard in urban and rural areas of Pakistan and India for the rebirth of forfeited sunnah among the Muslim masses. The golden chain of Naqshbandīyah Mujaddidia Sufis in Pakistan has been thriving for decades and different places served as its hubs. Khanqah Sirajia of Kundian Sharif is well known among the Ulema and Mashaikh of Pakistan for its indelible services. In this article, the author’s survey glimpses of contribution made by Khawaja Khan Muhammad (RA) of Kundian Sharif in effecting spiritual transformation of society in Pakistan. Khawaja Khan Muhammad (RA)has passed away a very famous elder of Silsila Alia Naqshbandīyah Mujaddidia, who lit the candle of this light of Prophethood from the Centre of Mianwali, Sirajia, on a global scale for half a century. Key words: Spiritual Transformation Naqshbandīyah Mujaddidia, Monastic system, Ulema and Mashaikh, Muslim Sufi fraternities.